Synthesis, characterization, antibacterial, antioxidant and anti-inflammatory activities of new 4-Aryl-2-amino-6-(4-hydroxy coumarin-3-yl) pyridine-3-carbonitriles derivatives (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This study aimed for the synthesis of 4-Aryl-2-amino-6-(4-hydroxy coumarin-3-yl) pyridine-3-carbonitriles 4 suitable for use as antibacterial, anti-oxidant and anti-inflammatory activities via a versatile, readily accessible 3-((2E)-3(aryl)prop-2-enoyl)-2H-chromen-2-one 3  which were prepared by refluxing 3-acetyl-4-hydroxy coumarin with aromatic aldehydes in chloroform in the presence of a catalytic amount of piperidine. Then the direct reaction of the obtained chalcones 3 with malonitrile in the presence of ammonium acetate in one step gave products 5 .The structures of the new compounds 3-4 were confirmed by elemental analysis, IR, and multinuclear/multidimensional NMR spectroscopy (1H, 13C-NMR, NOESY, HMBC) which allowed assignment of the complete network of proton and carbon atoms. Most of the new compounds 4 exhibit moderate antibacterial activity against Gram Negative bacterial strains (E. coli, K. pneumonia, S. typhi and S. flexneri). In addition, the compounds 4 were investigated for anti-oxidant activities by super oxide radical, DPPH (2,2-Diphenyl-1-picrylhydrazyl), and hydroxyl radical scavenging assays, where most of the compounds displayed significant antioxidant activities. Furthermore, these 4-Aryl-2-amino-6-(4-hydroxy coumarin-3-yl) pyridine-3-carbonitriles 4 were evaluated for anti-inflammatory activity by indirect haemolytic and lipoxygenase inhibition assays where compounds revealed good activity.